giúp mình với : (2x-3)mũ 3=27
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-1 . \(\dfrac{5}{27}\) - \(\left(3x.\dfrac{7}{9^{ }}\right)^3\) = -\(\dfrac{24}{27}\)
\(\Rightarrow\) \(\dfrac{-5}{27}\) - \(\left(3x.\dfrac{7}{9^{ }}\right)^3\) = \(\dfrac{-24}{27}\)
\(\Rightarrow\) \(\left(3x.\dfrac{7}{9^{ }}\right)^3\) = \(\dfrac{-5}{27}\) - \(\dfrac{-24}{27}\) = \(\dfrac{19}{27}\)
\(\Rightarrow\) \(3^3\) . \(\dfrac{7^3}{3^6}\) = \(\dfrac{19}{3^3}\)
\(\Rightarrow\) \(\dfrac{x^3.7^3}{3^3}\) = \(\dfrac{19}{3^3}\)
\(\Rightarrow\) \(x^3\) . \(7^3\) = 19
a) \(\left(2x+1\right)^3=27\)
\(\Leftrightarrow2x+1=3\)
\(\Leftrightarrow x=1\)
b) \(\left(2x-1\right)^3=125\)
\(\Leftrightarrow2x-1=5\)
\(\Leftrightarrow x=3\)
c) \(\left(x+1\right)^4=\left(2x\right)^4\)
\(\Leftrightarrow x+1=2x\)
\(\Leftrightarrow x=1\)
d) \(\left(2x-1\right)^5=x^5\)
\(\Leftrightarrow2x-1=x\)
\(\Leftrightarrow x=1\)
a. ( 2x + 1 )3 = 27
<=> ( 2x + 1 )3 = 33
<=> 2x + 1 = 3
<=> 2x = 2
<=> x = 1
b. ( 2x - 1 )3 = 125
<=> ( 2x - 1 )3 = 53
<=> 2x - 1 = 5
<=> 2x = 6
<=> x = 3
c. ( x + 1 )4 = 2x4
<=> x + 1 = 2x
<=> x = 1
d. ( 2x - 1 )5 = x5
<=> 2x - 1 = x
<=> x = 1
\(\frac{1}{9}\cdot27^x=3^x\)
\(3^x:27^x=\frac{1}{9}\)
\(\left(3:27\right)^x=\frac{1}{9}\)
\(\left(\frac{1}{9}\right)^x=\frac{1}{9}\)
\(\Rightarrow x=1\)
2x x 16 = 128
2x = 128 : 16
2 x = 8
2x = 23
3x : 9 = 27
3x = 27 x 9
3x =243
3x = 35
[ 2x + 1 ]3 = 27
2x3 + 13 = 27
2x3 +1 = 27
2x3 = 27 - 1
2x3 = 26
a, (-0,2)2 \(\times\) 5 - \(\dfrac{2^{13}\times27^3}{4^6\times9^5}\)
= 0,04 \(\times\) 5 - \(\dfrac{2^{13}\times3^9}{2^{12}\times3^{10}}\)
= 0,2 - \(\dfrac{2}{3}\)
= \(\dfrac{2}{10}\) - \(\dfrac{2}{3}\)
= - \(\dfrac{7}{15}\)
b, \(\dfrac{5^6+2^2.25^3+2^3.125^2}{26.5^6}\)
= \(\dfrac{5^6+4.5^6+8.5^6}{26.5^6}\)
= \(\dfrac{5^6.\left(1+4+8\right)}{26.5^6}\)
= \(\dfrac{1}{2}\)
a, (-0,2)2 ×× 5 - 213×27346×9546×95213×273
= 0,04 ×× 5 - 213×39212×310212×310213×39
= 0,2 - 2332
= 210102 - 2332
= - 715157
b, 56+22.253+23.125226.5626.5656+22.253+23.1252
= 56+4.56+8.5626.5626.5656+4.56+8.56
= 56.(1+4+8)26.5626.5656.(1+4+8)
= 1221
125:(2x-3)=25
-->2x-3=125:25
-->2x-3=5
-->2x=5+3
-->2x=8
-->x=8:2
-->x=4
k nha
\(125:\left(2x-3\right)=5^5:5^3\)
\(125:\left(2x-3\right)=5^2=25\)
\(2x-3=5\)
\(2x=8\)
\(x=4\)
x13 = 27.x16
=> x13 - 27x16 = 0
=> x13(1 - 27x3) = 0
=> \(\orbr{\begin{cases}x^{13}=0\\1-27x^3=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\27x^3=1\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x^3=\frac{1}{27}\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=\frac{1}{3}\end{cases}}\)
c) \(\left(\frac{1}{2}\right)^{2x-1}=\frac{1}{8}\)
=> \(\left(\frac{1}{2}\right)^{2x-1}=\left(\frac{1}{2}\right)^3\)
=> \(2x-1=3\)
=> \(2x=3+1\)
=> \(2x=4\)
=> \(x=4:2=2\)
a. ( 2x + 1 )2 = 49
<=> ( 2x + 1 )2 = 72
<=> 2x + 1 = 7
<=> x = 3
b. ( 2x - 1 )4 = 81
<=> ( 2x - 1 )4 = 34
<=> 2x - 1 = 3
<=> x = 2
c. ( x + 1 )3 = 2x3
<=> x + 1 = 2x
<=> x = 1
d. ( 2x + 1 )3 = 3x3
<=> 2x + 1 = 3x
<=> x = 1
( 2x + 1 )2 = 49
<=> ( 2x + 1 )2 = ( ±7 )2
<=> \(\orbr{\begin{cases}2x+1=7\\2x+1=-7\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-4\end{cases}}\)
( 2x - 1 )4 = 81
<=> ( 2x - 1 )4 = ( ±3 )4
<=> \(\orbr{\begin{cases}2x-1=3\\2x-1=-3\end{cases}}\Rightarrow\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
( x + 1 )3 = ( 2x )3
<=> x + 1 = 2x
<=> x - 2x = -1
<=> -x = -1
<=> x = 1
( 2x + 1 )3 = ( 3x )3
<=> 2x + 1 = 3x
<=> 2x - 3x = -1
<=> -x = -1
<=> x = 1
(2x-3)^3=27
ta thấy 3^3 = 27
nên x = 3
( 2 . 3 - 3 )^3 = 27
( 6 - 3 )^3 = 27
3^3 = 27
nha bạn
=27 nha bạn